The role of SELE gene polymorphism in ST-elevation myocardial infarction - N. P. Babushkina; A. M. Nikolaeva; A. D. Dolbnya; V. E. Shavrak; V. V. Ryabov (Вавиловский журнал генетики и селекции, 2025)
Ischemic heart disease (IHD) is an important medical and social problem. ST-elevation myocardial infarction (STEMI) is the most severe form of IHD, affecting all layers of the heart muscle. One of the diagnostic criteria for endothelial dysfunction in myocardial infarction is the level of sE-selectin, a cell adhesion molecule that recruits neutrophils and induces neutrophil inflammation.   The aim of this study is to investigate intronic polymorphisms rs5353, rs3917412 and rs1534904 of the E-selectin coding gene SELE in patients with STEMI. We have analyzed a group of patients with STEMI (n = 74) and a population sample of Tomsk (n = 136) as the control group.   The frequencies of the rs5353 genotypes in the SELE gene have shown statistically significant differences between patients and the control sample (p = 0.004). The CC genotype is a predisposing factor to STEMI (OR = 6.93, CI:95 % (1.84–26.04), χ2 = 8.69, p = 0.002). The analyzed mar kers were not studied previously in cardiovascular diseases (CVDs) and were rarely involved in association studies at all; there is no information on these SNPs in the leading databases. At the same time, all three variants, according to the RegulomeDB classification, belong to the functional class 1f, and are highly likely to have regulatory potential relative not only to the SELE gene, but also to other genes in the nearby region. The analysis of the functional significance of the studied markers has shown the presence of a region more extensive than one gene, which is co-regulated by the studied nucleotide substitutions. The association of rs5353 with STEMI identified in this study once again confirms the involvement of the SELE gene in the pathogenesis of CVDs. It is possible that this entire region of the genome may be involved indirectly in the pathogenesis of CVD through the systems of inflammation, immune response and DNA repair.